Insurgency: A Threat to Quality Assurance in Nigeria Secondary Education System - Ezeofor, Esther Toyin (NIU Journal of Humanities, 2020)
Quality education is the basis for national development; this is because education is an instrument par excellence for achieving national objectives. Secondary education is a transition stage of education that bridges between primary education and tertiary education. Secondary is intended to equip recipient with literacy and other basic skills which are needed for useful living in the society and for higher education. However, these feats are still mirages due to insurgency. Insurgency has undermined the journey to achieve quality secondary education through the various ills associated with it which include closure of schools, reduced school attendance, unsafe school environment, killing of teachers and students and destruction of school buildings and facilities among others. The paper attempts to examine how quality assurance in secondary education could be attained in the midst of insurgency. The conclusion and recommendations were also made in the paper. Keywords: Insurgency, quality assurance and Secondary Education